Indications for one-stage surgery in patients with combined occlusive-stenotic lesions of the coronary and brachiocephalic artery - Usenko, A. Y.; Gabrielyan, A. V.; Nikulnikov, P. I.; Beleevich, V. V.; Ratushnyuk, A. W. (Ukrainian Journal of Cardiovascular Surgery, 2016)
This article contains the results of medical pre-assesment and surgery of 35 patients with. Combined carotid and coronary arterial diseases. It includes comparative analysis and scientifically proven indications for simultaneous and staged surgical procedures in these patients.